Perlindungan Hukum Terhadap Whistleblower Dalam Tindak Pidana Narkotika - Silvia Hainia; Abdurrakhman alhakim (Jurnal Hukum Sasana, 2022)
The spread of drugs and illegal drugs in Indonesia is of great concern and concern to the public, and the media is almost full of drug trafficking and arrests for other criminal activities. In performing duties as police law enforcement officers, they need the Code of Ethics as long as it guides in daily practice. Regulations related to the Police Code of Ethics can be found in the Law on the Indonesian National Police Number 2 of 2002, Regulation of the Chief of the National Police Number 8 of 2006, and Number 7 of 2006. The goal of Indonesia's national development is to create a truly just, peaceful, safe, and secure society. and prosper based on Pankashira and the 1945 Constitution of the Republic of Indonesia. 2009 35 concerning Narcotics. The method used in this research is the normative legal method or literature based on the laws and regulations related to the Narcotics Law Number 35 of 2009. The approaches that are highlighted are valid literature studies and textual approaches derived from case studies and written literature, namely a study that distinguishes between what is contained in the text or literature with what is contained therein. To ensure the safety of the reporter, law must regulate the safety of the reporter.